The Presence of Unusual Foramina in the Femoral Intercondylar and Trochanteric Fossae on Skeletonized Individuals from Tanzania - Jilala, Wilson; Ngassapa , David; Hamad, Ali (Tanzania Journal of Science, 2023)
According to the standard nomenclature, skeletal land marks are all identified by their given names in the world of human skeletal anatomy. But it is also clear that the discovery of new anatomical features continues because human beings have so many anatomical variations caused by genetics, functions, geographical adaptations, and diseases; they are all described and given names. Therefore, an anatomical feature that is rare and undescribed is certainly a discovery and it deserves to be recorded. The discovery of anatomical features on the epiphyseial ends of the femur reported here adds two new names, namely the intercondylar fossa foramen and the trochanteric fossa foramen in that long list of human skeletal anatomical structures. The intercondylar fossa foramen is an outlet found in the intercondylar fossa of the distal femur. It passes through the diaphysis of the femur and emerges in the trochanteric fossa of the femoral neck; and vice versa is the trochanteric fossa foramen. This feature was first observed on one skeletonized archaeological individual and later on five cadaveric remains. There seems to be a presence of this anatomical variation within the Tanzanian population. Only a small percentage of people have this unusual anatomical feature of the intercondylar fossa foramen, which might be a developmental ossification failure or a particular genetic-based trait. These features were assessed in the laboratory of the Anatomy Department at the Muhimbili University of Health and Allied Sciences (MUHAS) using a Dino-lite digital microscope and X-ray images.